2020
DOI: 10.3389/fmicb.2020.00838
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Postzygotic Evolution of the Mitochondrial Genome in Hybrids of Saccharomyces Species Isolated by Double Sterility Barrier

Abstract: Eukaryotic species are reproductively isolated by sterility barriers that prevent interspecies fertilization (prezygotic sterility barrier) or the fertilization results in infertile offspring (postzygotic sterility barrier). The Saccharomyces species are isolated by postzygotic sterility barriers. Their allodiploid hybrids form no viable gametes (ascospores) and the viable ascospores of the allotetraploids cannot fertilize (conjugate). Our previous work revealed that this mechanism of reproductive isolation di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 109 publications
(207 reference statements)
2
6
0
Order By: Relevance
“…As observed in previous studies on allotetraploid yeast (Greig et al, 2002;Sebastiani et al, 2002;Antunovics et al, 2005;Pfliegler et al, 2012;Karanyicz et al, 2017;Szabó et al, 2020;Naseeb et al, 2021) there appeared to be no post-zygotic barrier to reproduction with the F1 hybrid investigated here. The ability to produce viable spores among the F1 spore clones was also limited to tetraploid strains (via endomitosis (Sebastiani et al, 2002) or, as is most likely the case here, self-fertilization of homo-or hemizygous diploid spores).…”
Section: Discussionsupporting
confidence: 86%
“…As observed in previous studies on allotetraploid yeast (Greig et al, 2002;Sebastiani et al, 2002;Antunovics et al, 2005;Pfliegler et al, 2012;Karanyicz et al, 2017;Szabó et al, 2020;Naseeb et al, 2021) there appeared to be no post-zygotic barrier to reproduction with the F1 hybrid investigated here. The ability to produce viable spores among the F1 spore clones was also limited to tetraploid strains (via endomitosis (Sebastiani et al, 2002) or, as is most likely the case here, self-fertilization of homo-or hemizygous diploid spores).…”
Section: Discussionsupporting
confidence: 86%
“…Mitochondrial-nuclear interactions have been reported as having a major role in phenotypic variation both in intra-species and inter-species yeast hybrids (E. P. Baker et al 2019; Chou et al 2010; Hewitt et al 2020; Hsu and Chou 2017; Lee et al 2008; X. C. Li et al 2019; Paliwal et al 2014), affecting respiration (Albertin et al 2013) fermentation properties (Hewitt et al 2020; Solieri et al 2008), progeny fitness (Zeyl et al 2005; Zeyl 2006), reproductive isolation (Chou and Leu 2010; Lee et al 2008; Szabo et al 2020) and nuclear transcription (Hewitt et al 2020). Studies on inter-species yeast hybrids in the lab have shown a correlation between the origin of the mitochondrial genome and the higher stability of one of the nuclear genomes (Antunovics et al 2005; Karanyicz et al 2017; Peris et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, SKO1, a basic leucine zipper transcription factor, mapped in S. eubayanus alleles of Sc/Sem segregants, has been described having a major role in mediating HOG pathway-dependent osmotic regulation (Rep et al 2001). (Albertin et al 2013) fermentation properties (Hewitt et al 2020;Solieri et al 2008), progeny fitness (Zeyl et al 2005;Zeyl 2006), reproductive isolation (Chou and Leu 2010;Lee et al 2008;Szabo et al 2020) and nuclear transcription (Hewitt et al 2020). Studies on interspecies yeast hybrids in the lab have shown a correlation between the origin of the mitochondrial genome and the higher stability of one of the nuclear genomes (Antunovics et al 2005;Karanyicz et al 2017;Peris et al 2020).…”
Section: Phenotypic Diversity Of Tetraploid Hybrids Is Underpinned Bymentioning
confidence: 99%
“…The hybrids usually had parental mitotypes or, less frequently, recombinant mitotypes (e.g. 16,[30][31][32][33][34] ). In this study both types of hybrids were homoplasmic.…”
Section: Discussionmentioning
confidence: 99%